EFFECT DIGITAL BASED LEARNING VIDEO MEDIA ON STUDENT CIVICS LEARNING OUTCOMES IN GRADE IV ELEMENTARY SCHOOL - Eva Pasaribu; Minar Trisnawati Tobing (Sensei International Journal of Education and Linguistic, 2023)
The purpose of this study was to determine the effect of video media on student learning outcomes in Civics learning class IV SD Negeri 091542 Hutabayu. This research is an experimental research with Quasi Experimental Design. The design used in this research is Pretest-Postest. The sample in this experimental class research was fourth grade students at Public Elementary School 091542 Hutabayu and the control class research sample was fourth grade students at SD Negeri 091524 PNP Tonduhan. Based on the results of the analysis and discussion of the research data, the results of hypothesis testing are obtained with the t-test, where t count = 2.30 if the significant value (2-tailed) <0.05, then there is a significant difference between student learning outcomes in the experimental class and the control class . The result of this study is the significance value (2-tailed) = 0.02. then H0 is rejected and Ha is accepted. Based on these results it can be concluded that there is an influence of video media on student learning outcomes in thematic learning class IV SD Negeri 091542 Hutabayu.